Hypertrophic Obesity and Subcutaneous Adipose Tissue Dysfunction - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: Over the past 50 years, scientists have recognized that not all adipose tissue is alike, and that health risk is associated with the location as well as the amount of body fat. Different depots are sufficiently distinct with respect to fatty-acid storage and release as to probably play unique roles in human physiology. Whether fat redistribution causes metabolic disease or whether it is a marker of underlying processes that are primarily responsible is an open question.CONTENT: The limited expandability of the subcutaneous adipose tissue leads to inappropriate adipose cell expansion (hypertrophic obesity) with local inflammation and a dysregulated and insulin-resistant adipose tissue. The inability to store excess fat in the subcutaneous adipose tissue is a likely key mechanism for promoting ectopic fat accumulation in tissues and areas where fat can be stored, including the intra-abdominal and visceral areas, in the liver, epi/pericardial area, around vessels, in the myocardium, and in the skeletal muscles. Many studies have implicated ectopic fat accumulation and the associated lipotoxicity as the major determinant of the metabolic complications of obesity driving systemic insulin resistance, inflammation, hepatic glucose production, and dyslipidemia.SUMMARY: In summary, hypertrophic obesity is due to an impaired ability to recruit and differentiate available adipose precursor cells in the subcutaneous adipose tissue. Thus, the subcutaneous adipose tissue may be particular in its limited ability in certain individuals to undergo adipogenesis during weight increase. Inability to promote subcutaneous adipogenesis under periods of affluence would favor lipid overlow and ectopic fat accumulation with negative metabolic consequences.KEYWORDS: obesity, adipogenesis, subcutaneous adipose tissue, visceral adipose tissue, adipocyte dysfunction